On the Way Between Utopia and Totalitarianism. The Bolshevik Constitution of 1918 as a Model of Socialist Constitutionalism - A. Bosiacki (BRICS Law Journal, 2019)
Although Russian constitutionalism has a rich past and present, its place on the global map of the history of constitutional thought is not clearly defined yet. This paper contributes to the analysis of the early stages of development of Russian constitutionalism. The first Russian act resembling a “true” Constitution was the Constitution of the RSFSR of 1918. It was aimed not at the realization of the ideas of constitutionalism, but at the formation of a model of a totalitarian state. It sanctioned radical social changes and led to the liquidation of the concept of the division of power and the omnipotence of the nonconstitutional organs (like VChK, various “tribunals”). However, this act and its ideological sources deserve a more in-depth analysis. First of all, its utopian ideas about the new social system have to be identified and examined. The analysis shows that the 1918 Constitution reflects Lenin’s fascination with the ideas of direct democracy drawn from the experience of the Paris Commune and the French Revolution after 1789. In particular, it is about the perception of the idea of unlimited supreme power, undivided and combined, and at the same time federated in the form of loose communes. If we consider the range of constitutional ideas, the Bolsheviks adopted nothing more original that the concept of Rousseau’s national sovereignty. However, the implementation of utopian ideas ended with the creation of a totalitarian system, which contemporaries called “state despotism,” more powerful than the despotism of the Russian Empire.